Pengaruh Struktur Aset, Inovasi Dan Teknologi, Biaya Agensi, Ukuran Perusahaan Dan Pertumbuhan Perusahaan Terhadap Leverage - Rahma Putra, Wili; Munandar, Agus (GEMA EKONOMI, 2023)
Until now, companies that are included in the LQ45 category are the companies that attract large investors. Therefore, companies must have the ability to manage the company's sources of financing well and avoid company losses. Therefore, the aim of this study is to understand the empirical impact of asset structure, innovative technology, agency costs, firm size and firm growth on the leverage ratio. LQ45 companies listed on the Indonesia Stock Exchange between 2019 and 2021. This research uses causal benchmarking. The sample for this research is LQ45 member companies listed on the Indonesia Stock Exchange for the 2019-2021 period, using the target sampling method. There are 11 companies that meet the screening criteria for the research sample and 33 financial reports. The results show that asset structure, innovative technology, agency costs and size the company has a significant effect on the leverage ratio, while the company's growth variable has no significant effect on the leverage ratio.